2000
DOI: 10.1021/np0000872
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship of Polyisoprenyl Benzophenones from Garcinia pyrifera on the Tubulin/Microtubule System

Abstract: Microtubule disassembly inhibitory properties have been established for the known polyisoprenylated benzophenones xanthochymol (1a) and guttiferone E (1b). The compounds were isolated from the fruits of Garcinia pyrifera collected in Malaysia. A structure-activity relationship study, including natural and semisynthetic derivatives, delineated some structural features necessary for the interaction with tubulin within this compound class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 24 publications
4
89
0
3
Order By: Relevance
“…For example, guttiferones A-F were shown to reduce the cytopathic effects in HIV-infected cells. [14] Guttiferone E inhibits the depolymerization of the microtubules into tubulin, [15] and guttiferone I was reported to be a ligand of liver X receptors. [13a] Since SIRT1 is a regulator of HIV transcription [6] and SIRT2 a tubulin deacetylase, [7a] we assayed the isolated guttiferone G for inhibitory activity against sirtuin.…”
Section: Dedicated To Professor Peter Welzel On the Occasion Of His 7mentioning
confidence: 99%
“…For example, guttiferones A-F were shown to reduce the cytopathic effects in HIV-infected cells. [14] Guttiferone E inhibits the depolymerization of the microtubules into tubulin, [15] and guttiferone I was reported to be a ligand of liver X receptors. [13a] Since SIRT1 is a regulator of HIV transcription [6] and SIRT2 a tubulin deacetylase, [7a] we assayed the isolated guttiferone G for inhibitory activity against sirtuin.…”
Section: Dedicated To Professor Peter Welzel On the Occasion Of His 7mentioning
confidence: 99%
“…1 These compounds can be divided principally into two classes, with type A possessing a bridgehead acyl group adjacent to a quaternary center, and type B having two bridgehead isoprenyl chains and an acyl group bound to C-3. 2 Moreover, irrespective of the type (A or B), some PPAPs have the 7-substituent either in an equatorial exo position (i.e., nemorosone, 2 clusianone, 3 or aristophenone 4 ) or in an axial endo position (i.e., 7-epi-nemorosone 5 or xanthochymol 6 ). Finally, natural products with a tricyclic core, with an oxygen heterocycle, are also found as in the case of garsubellin A 7 or of hyperibone I 8 with their 4-oxa-tricyclo [6.3.1.0 1,5 ]dodec-5-ene-7,12-dione skeletons.…”
Section: Introductionmentioning
confidence: 99%
“…10e Our interest in the field of PPAPs came from the observation that xanthochymol was active in a tubulin disassembly inhibition test. 6 After our work leading to the isolation of oblongifolins A-D, 12 we undertook synthetic studies toward type B PPAPs. 11,13 We previously showed that the boron trifluoride catalyzed Effenberger α,α'-annulation 14 of isomeric 2,4,6-triprenyl-3,3-dimethylcyclohexanones TMS enol ethers 1 with malonyl dichloride allowed the formation of the bicyclo[3.3.1]nonane-2,4,9-trione 2 with an equatorial prenyl group.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that compounds 1 and 4 both exhibit antiproliferative characteristics. The antimicrotubule drug docetaxol was used as a control since type B PPAP compounds have been demonstrated to exhibit an inhibitory activity of the tubulin assembly of carcinoma cells [17]. In conclusion, 1 and 4 have potential for development as anticancer candidates, and future works to study their modes of action as antimictrotubule agents should be emphasized.…”
mentioning
confidence: 99%